2000
DOI: 10.1577/1548-8675(2000)020<0226:mopihn>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Paddlefish in Hoop Nets in the Lower Missouri River, Missouri

Abstract: Mortality of paddlefish Polyodon spathula collected in hoop nets was observed in the lower Missouri River, Missouri, in 1997. Unbaited hoop nets of three mesh sizes (2.5, 5.0, and 7.5-cm, bar measure) were fished from March to October in two habitats (insidebend steep-cut banks and outside-bend revetted banks). In 462 net-days of effort we caught 23 paddlefish in 5.0and 7.5-cm-mesh nets but none in the 2.5-cm-mesh nets; 35% of the paddlefish collected were found dead. Most paddlefish (90%) were collected along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…They also found that the larger-mesh hoop nets detected bigger fish on average (316 mm) than smaller-mesh hoop nets (266 mm). Hoop nets also are effective for capturing species such as channel catfish (Vokoun and Rabeni 2001;Vokoun and Rabeni 2002) and paddlefish (Dieterman et al 2000) in prairie rivers and are a useful tool for assessing population characteristics when different mesh sizes are used concurrently.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that the larger-mesh hoop nets detected bigger fish on average (316 mm) than smaller-mesh hoop nets (266 mm). Hoop nets also are effective for capturing species such as channel catfish (Vokoun and Rabeni 2001;Vokoun and Rabeni 2002) and paddlefish (Dieterman et al 2000) in prairie rivers and are a useful tool for assessing population characteristics when different mesh sizes are used concurrently.…”
Section: Discussionmentioning
confidence: 99%
“…However, longer deployments do not necessarily result in greater mortality (Uhlmann & Broadhurst, ), and these relationships have rarely been tested (Barber & Cobb, ). Becoming gilled within the trap material can be an issue for certain species regardless of deployment duration (e.g., Dieterman, Baird, & Galat, ); it is therefore important to choose a mesh size that minimizes mortality to non‐target species while not affecting CPUE. Where barotrauma is of concern, reducing ascent rates when retrieving traps may reduce effects of barotrauma, but this is not a practical solution for most commercial operations (Stewart, ).…”
Section: Capture Stressors and Their Mitigation Potential By Fishing mentioning
confidence: 99%
“…Efforts to improve recreational walleye fisheries resulted in uneconomical commercial fisheries because commercial fishers often exceeded their walleye bycatch quota before they realized their lake whitefish quota. Paddlefish, Polyodon spathula, bycatch rates were described in a Missouri River hoopnet fishery targeting buffalo, Ictiobus spp., and exotic carps (Dieterman et al, 2000); those authors predicted one paddlefish would be caught and killed for every 37 net-days of fishing effort. We are unaware of any published reports on bycatch rates for commercially exploited paddlefish (i.e., the number of paddlefish discarded), nor are we aware of any studies describing rates of bycatch mortality for paddlefish captured in gillnets.…”
Section: Introductionmentioning
confidence: 99%